507 a. Determining the marginal cost differences and potential areas of improvement for a telerehabilitation versus outpatient occupational therapy session for stroke survivors. (April 2022) - Morrow, Corey; Woodbury, Michelle; Simpson, Kit
Abstract : OBJECTIVES/GOALS: The objective of this study was to estimate the cost differences of a telerehabilitation versus outpatient session. A secondary objective was to identify areas to improve telerehabilitation delivery efficiency. We aim to improve the translation/adoption of telerehabilitation for clinical use. METHODS/STUDY POPULATION: This study used a time-driven activity-based costing (TDABC) approach including 1) observation of rehabilitation sessions and creation of manual time stamps, 2) structured and recorded interviews with two occupational therapists familiar with outpatient therapy and two therapists familiar with telerehabilitation, 3) collection of standard wages for providers, and 4) the creation of an iterative flowchart of both an outpatient and telerehabilitation session care delivery process. This study followed the reporting guidelines to ensure a standardization for TDABC research. RESULTS/ANTICIPATED RESULTS: Overall, telerehabilitation ($225.41) was more costly than outpatient therapy ($168.29) per session for a cost difference of $57.12. Primary time drivers of this finding were initial phone calls (0 mins for OP therapists versus 35 mins for TR) and post documentation (5 mins for OP versus 30 mins for TR) demands for telerehabilitation. DISCUSSION/SIGNIFICANCE: Telerehabilitation is an emerging platform with the potential to reduce costs, improve healthcare inequities, and facilitate better patient outcomes. Improvements in documentation practices, staffing, technology, and reimbursement structuring would allow for a more successful translation.